Satisfaction with Human Resource Practices: Evidence from Banking Industry of Nepal - Khadka, Sherjung (Tribhuvan University Journal, 2013)
This study is based on quantitative research design. Simple random sampling technique is used in this study. The data were gathered with the help of a well structured questionnaire. Cronbach’s alpha was used to test the reliability of the questionnaire. This study is primarily concern with employee satisfaction with HR practices. On an average 77.85 per cent, 73.90 per cent, 87.68 per cent and 71.93 percent employees satisfied with employee benefits, recruitment and selection, job assignment and performance appraisals respectively and 11.83 per cent, 19.15 percent, 12.04 per cent, and 21.53 per cent employees neutrally satisfied with these HR practices respectively. Likewise, only 10.32 per cent, 6.95 per cent, 0.28 per cent, and6.54 per cent employees dissatisfied with the same. Thus, the majority of employees satisfied with HR practices of the banking industry of Nepal.